Jarimatika Extracurricular Method in Developing Early Numeracy Skills: Implementation and Challenges in Islamic Early Childhood Education - Cindy Julia Sari; Mustakimah; Mursid (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
This research was motivated by the need to examine how the Jarimatika extracurricular activity contributes to the development of numeracy skills in children at RA Masjid Al-Azhar. The purpose of this study was to describe the implementation process, children's responses, improvements in numeracy skills, and challenges faced during the activity. The methods and techniques used were descriptive qualitative, and data were collected through observation, interviews, and documentation involving Jarimatika instructors and the principal at RA Masjid Al-Azhar. The researcher revealed that Jarimatika is a structured and concrete method that improves children's accuracy, speed, concentration, and confidence in performing counting operations. Although challenges arise regarding children's limited attention span, this is successfully overcome through various strategies such as quizzes, finger warm-ups, and interactive activities. The results of the study suggest that Jarimatika is a valuable alternative to support early numeracy and can be integrated into learning programs to create more engaging and developmentally appropriate mathematical experiences. Children's responses during the activity generally increased very positively. They appeared enthusiastic about each step, displaying happy expressions, actively answering questions, and even initiating the use of their fingers to count before instructions were given. Increased engagement was also seen in children who were initially passive but became more active after the instructor introduced the Jarimatika method with games like a quick answer contest or guessing numbers.